2021
DOI: 10.3389/fneur.2021.729509
|View full text |Cite
|
Sign up to set email alerts
|

Aging With Cerebral Palsy: A Photovoice Study Into Citizenship

Abstract: Background: Adults with cerebral palsy (CP) may experience an increasing impact of their disability on daily life and this may interfere with their citizenship. Citizenship is a layered construct. Next to formal and theoretical significations, and civil rights acts such as the UN Convention on the Rights for Persons with Disabilities (CRPD), the meaning of citizenship is formed by the person themselves. The present study aimed to gain insight into what citizenship means for adults with CP 40 years or older and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…This included issues faced, such as insufficiencies in healthcare and access to rehabilitation services, indicating a view that people with neurological conditions may be treated differently. In a number of papers, the complicated health system left people living with a neurological condition confused as to why care stopped suddenly and no more services were available (Gunton et al, 2021; LaDonna et al, 2015; Maratos et al, 2016; Roger et al, 2018; Tornbom et al, 2019; van Heijningen et al, 2021). Tornbom et al (2019) also found that many years after a stroke, participants still experienced improvements through persistent rehabilitation, and wished for more interactive rehabilitation training, including collaborative forms of rehabilitation being suggested in the long-term phase of stroke.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This included issues faced, such as insufficiencies in healthcare and access to rehabilitation services, indicating a view that people with neurological conditions may be treated differently. In a number of papers, the complicated health system left people living with a neurological condition confused as to why care stopped suddenly and no more services were available (Gunton et al, 2021; LaDonna et al, 2015; Maratos et al, 2016; Roger et al, 2018; Tornbom et al, 2019; van Heijningen et al, 2021). Tornbom et al (2019) also found that many years after a stroke, participants still experienced improvements through persistent rehabilitation, and wished for more interactive rehabilitation training, including collaborative forms of rehabilitation being suggested in the long-term phase of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Obstacles and obstructions that posed threats to physical safety (e.g., narrow aisles, sidewalks in poor condition, lack of outdoor lighting, or lack of accessible entrances) also presented c hallenges . Without change around these issues, people living with neurological conditions could be hindered from living successfully due to the negative impact on their confidence and independence (Balakrishnan et al, 2017; Barclay-Goddard et al, 2012; Bishop et al, 2013; Evans et al, 2016; Genoe & Dupuis, 2013; Gunton et al, 2021; Maratos et al, 2016; Seetharaman et al, 2021; Tornbom et al, 2019; van Heijningen et al, 2021; Walker et al, 2020). By not addressing the social needs required for change, concerns around physical environmental barriers could likely prevent activities such as going to shops or restaurants and further isolate people living with neurological conditions from society, resulting in a person feeling ignored and not important enough for society to address such issues, and leaving a sense of disappointment with how people living with a neurological condition are being treated by society.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cobigo and colleagues (2016) interviewed people with intellectual disabilities about their views on inclusion, which resulted in four items rated as highly relevant to all respondents: a) belonging to a group, (b) having interpersonal relationships, (c) being accepted as an individual, and (d) having reciprocal relationships. This corresponds to the themes that people with disabilities have identified as being key for involvement in society: belonging, being valued, accessibility, and having agency (Yeung, Passmore & Packer 2008;van Heijningen et al 2021). So, despite appealing descriptions and key elements, existing definitions and practices of inclusion are not (enough) based on the perspectives of the people concerned (Cobigo et al 2016;Hammell 2013;Fadyl, Teachman & Hamdani 2020).…”
Section: The Perspective Of Care-usersmentioning
confidence: 98%